Sudden Cardiac Death, Aborted, in Healthy 34-Year-Old Male - Shah, Hitesh (Medknow Publications & Media Pvt Ltd, 2014)
A 34-year-old male, non-hypertensive, non-diabetic, had a sudden onset of cardiac arrest, he was revived and then referred to a cardiologist at an advanced center for further care. His 2D echo revealed hypertrophic obstructive cardiomyopathy, all the other investigations were normal. His father was also found to have a similar condition however the father was asymptomatic. The patient underwent an automated implantable cardioverter-defibrillator implantation and was advised the necessary precautions and care.